Paradoxically Greater Persistence of HIV RNA-Positive Cells in Lymphoid Tissue When ART Is Initiated in the Earliest Stage of Infection. (11th March 2022) - Kroon, Eugène; Chottanapund, Suthat; Buranapraditkun, Supranee; Sacdalan, Carlo; Colby, Donn J; Chomchey, Nitiya; Prueksakaew, Peeriya; Pinyakorn, Suteeraporn; Trichavaroj, Rapee; Vasan, Sandhya; Manasnayakorn, Sopark; Reilly, Cavan; et al.
Abstract: Starting antiretroviral therapy (ART) in Fiebig 1 acute HIV infection limits the size of viral reservoirs in lymphoid tissues, but does not impact time to virus rebound during a treatment interruption. To better understand why the reduced reservoir size did not increase the time to rebound we measured the frequency and location of HIV RNA + cells in lymph nodes from participants in the RV254 acute infection cohort. HIV RNA + cells were detected more frequently and in greater numbers when ART was initiated in Fiebig 1 compared to later Fiebig stages and were localized to the T-cell zone compared to the B-cell follicle with treatment in later Fiebig stages. Variability of virus production in people treated during acute infection suggests that the balance between virus-producing cells and the immune response to clear infected cells rapidly evolves during the earliest stages of infection. Clinical Trials Registration : NCT02919306. Abstract : People treated in the very earliest stages of acute HIV infection have significantly higher frequencies of viral RNA-positive cells detected in lymphoid tissue after a year of ART compared to treatment in later stages.